PENGARUH MODEL PEMBELAJARAN ARTIKULASI TERHADAP KETERAMPILAN BERBICARA KELAS IV PADA MATA PELAJARAN BAHASA INDONESIA SDN GUGUS 01 KECAMATAN BRANG REA TAHUN AJARAN 2020/2021 - Duwi Ratnasari; Ida Bagus Kade Gunayasa; Heri Hadi Saputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2022)
This study aims to determine the effect of the learning model on the speaking skills of fourth grade students of SDN Gugus 1, Brang Rea District, 2020/2021 academic year. The results of this study are expected to be useful theoretically and practically. This type of research is an experimental study with a quasi experimental design type nonequivalent control group design. The population of this study were all grade V students of SDN Gugus 1, Brang Rea Subdistrict, 2020/2021 academic year with a total of 53 students consisting of 28 class IV SDN Kejawat as the control class and the fourth class SDN Bree as the experimental class with 25 students. The sampling technique of this research is nonprobality sampling type saturated sampling with a sample class IV SDN Gugus 1 District Brang Rea. The data collection method in this study was a test of students' speaking skills using an oral test (pretest-posttest). Data analysis was carried out by using the normality test, homogeneity test and hypothesis testing using the polled variance t-test formula. Hypothesis testing Pretest control and experiment got a value that is 3.11> 2.013 at the 5% significance level. While the control and experimental posttest was 3,431> 2013 at the 5% significance level. In accordance with the hypothesis testing, namely tcount> ttable, Ho is rejected and Ha is accepted. Thing. Therefore, it can be concluded that there is an effect of the learning model on the speaking skills of fourth grade students of SDN Gugus 1, Brang Rea District, 2020/2021 school year.